PELATIHAN PENGGUNAAN ACCOUNTING SOFTWARE DALAM MENGELOLA INFORMASI KEUANGAN PADA SMK ERA UTAMA PANCUR BATU - Enda Natasha S Pandia, Sonya; Juita Wailan’ An, Evi; Salsabila, Zulpa (Universitas PGRI Yogyakarta, 2023)
The impact of technology in the world of education, especially in the field of accounting. Advances in Information Technology (IT) have an impact on the application and development of accounting science. The emergence of terms such as ebusiness and enterprise systems shows that the world of accounting will become increasingly complex, not just managing journals and preparing financial reports. The role of an accountant can cover three areas, namely designer, user and examiner. Therefore, vocational schools in the field of accounting need to have up-to-date knowledge regarding IT developments in accounting. Pantia PkM conducted a survey, the results found partner problems, namely, the need to improve the abilities and skills of Era Utama Pancur Batu Vocational School students in using IT and required knowledge sharing activities related to transaction management activities to producing financial reports using Accurate Software. Based on this problem, the solution given is to carry out community service activities (PkM) in the form of training in the form of workshops on using the Accurate 5 application. The aim of this PkM is to increase students' information technology knowledge and abilities in operating the Accurate Version 5 application. keyword: Accurate Software; accounting; Financial Information;